2012
DOI: 10.5923/j.als.20120203.06
|View full text |Cite
|
Sign up to set email alerts
|

On the Morphological and Genotypic Variations of Two Congeneric species of Banana Aphid Pentalonia (Homoptera: Aphididae) from India

Abstract: Banana aphid Pentalonia has already been described in its two taxonomic fo rms fro m hosts of Zingiberaceae and Araceae were regarded as separate taxa, P. nigronervosa Coquerel and P. caladii van der Goot, respectively, based on morphological and molecu lar differences. Between the two species of Pentalonia tested in our earlier study, the nigronervosa species expressed fitness for banana host plants and the caladii species for taro host plant suggesting strong genotype(aphids)-environment(host plants) interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…one species of aphids was found: Pentalonia caladii van der Goot, 1917. Pentalonia caladii was known and found in taro plants; the aphids formed colonies under the surface of young and older leaves (Bhadra and Agarwala 2014). This study found that the occupied leaf areas did not display severe symptoms; the aphids were yellow-green to dark green.…”
Section: Discussionmentioning
confidence: 65%
“…one species of aphids was found: Pentalonia caladii van der Goot, 1917. Pentalonia caladii was known and found in taro plants; the aphids formed colonies under the surface of young and older leaves (Bhadra and Agarwala 2014). This study found that the occupied leaf areas did not display severe symptoms; the aphids were yellow-green to dark green.…”
Section: Discussionmentioning
confidence: 65%